THE DIFFERENCE OF COCONUT VARIETIES AND TEMPERATURE IN CARRAGEENAN EXTRACTION FROM SEAWEED (EUCHEUMA COTTONII) (Jurnal Teknologi Pangan, 2022)
The use of coconut water as a natural solvent is needed in the extraction of carrageenan, as an alternative to the use of KOH as a synthetic solvent. This study aims to examine the effect of using coconut water from two different varieties of coconuts as solvents and different extraction temperature in extracting carrageenan. The study was conducted in 2 steps. Step 1 was carrageenan carrageenan from Eucheuma cottonii with coconut water solvent, then analyzing the physicochemical characteristics of the carrageenan produced such as yield, gel strength, viscosity, moisture and ash content. Step 2 was the application to chicken meatball. The results showed that the the best carrageenan in this study was carrageenan that was extracted with solvent from hybrid coconut water and temperature of 80°C with a yield of 75.48%, gel strength of 579.874 g/cm2, viscosity of 5.1 cps, moisture content of 10.85% and ash content 11.32%. Application of the best carrageenan from the best treatment produced chicken meatballs with chewiness of 49.26 N, brightness of 73.35, a value of 0.95 and b value of 11.6. The use of coconut water can be used as an alternative natural solvent in extracting carrageenanKeywords : carrageenan, chicken meatball, coconut water, natural solvent, temperature DOI : https://doi.org/10.33005/jtp.v16i1.2895